Measuring Socioeconomic Inequality Changes in Child Mortality in Iran: Two National Surveys Inequality Analysis - Mostafa AMINI RARANI; Arash RASHIDIAN; Mohammad ARAB; Ardeshir KHOSRAVI; Ezatollah ABBASIAN (Tehran University of Medical Sciences, 2018)
Abstract Background: We aimed to measure changes in socioeconomic inequality in child mortality in Iran. Methods: A secondary data analysis of two Demographic and Health Surveys (DHS 2000 and 2010) was undertaken. Neonatal, infant and under-5 mortality rates were estimated directly from complete birth history. Economic quintiles were constructed using principal component analysis. Changes in inequality were measured using odds ratios, mortality rates, and concentration curves and indices. Results: Based on the compared measures, inequalities in neonatal, infant, and under-5 mortality declined between the two surveys. The poorest-to-richest neonatal, infant and under-5 mortality odds ratios in 2000 were 1.69 (95% CI= 1.3-2.07), 2.85 (95% CI= 1.96-4.1) and 1.98 (95% CI= 1.64-2.3), respectively. Whereas these mortality odds ratios in 2010 had fallen to 1.65 (95% CI= 0.95-2.9), 1.47 (95% CI=0.5-4) and 1.85 (95% CI=1.13-3), respectively. Moreover, mortality rates in all economic quintiles experienced a decreasing trend. Neonatal, infant, and under-5 mortality concentration indices in 2000 were -0.15, -0.26, and -0.17 respectively. Whereas concentration indices in 2010 had dropped to -0.13, -0.11, and -0.14, respectively. Concentration curves dominance test revealed that there was a statistically significant reduction in inequality in infant and under-5 mortalities. Conclusion: Despite substantial reduction in child mortality rates and narrowing of the gap between poor and rich people, socioeconomic inequality in child mortalities disfavoring worse-off groups still exists. Combination of child health-related efforts that aim to reach to those children born in poor households alongside with pro-equity programs in other sectors of society may further reduce infant, under-5, and particularly neonatal mortality across economic quintiles in Iran.